Pengaruh Kecanggihan Teknologi Informasi dan Pengetahuan Pengguna Terhadap Efektivitas Sistem Informasi Akuntansi : (Studi Kasus pada Koperasi yang ada di Wilayah Cimahi Utara) - Jejen Jaenudin; Nastiti Rizky Shiyammurti (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research was conducted in cooperatives in the North Cimahi region. The purpose of this study was to examine the effect of sophistication of information technology and management knowledge on the effectiveness of accounting information systems in cooperatives in the North Cimahi region. The population in this study were customers of cooperative management in the North Cimahi region, with a sample of 63 administrators. The sampling technique used was the census sampling method or the saturated sample. The research design used descriptive and associative methods. The results of the descriptive analysis showed that the average score of the information technology sophistication variable (X1) was 196 categorized as